Pengaruh Tata Ruang (Layout) Dan Komunikasi Kantor Terhadap Semangat Kerja Pegawai Di Kantor Kecamatan Tasikmadu Kabupaten Karanganyar - Arwanda Tulus Kurniyanto; Tri Murwaningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to: (1) determine the influence of office layout on employee work morale at the Tasikmadu District Office, Karanganyar Regency (2) determine the influence of communication on employee work morale at the Tasikmadu District Office, Karanganyar Regency (3) determine the influence of office layout and communication overall. together on the work spirit of employees at the Tasikmadu District Office, Karanganyar Regency. This research uses quantitative methods, the population in this research is all employees at the Tasikmadu District Office, Karanganyar Regency. The sampling technique was 37 at the Jaten District Office, Karanganyar Regency using saturated samples. The data collection technique uses a questionnaire technique. Data analysis techniques use the classic assumption test, t test, f test, multiple regression analysis. The results of this research are (1) there is an influence of office layout (layout) on the work spirit of employees at the Tasikmadu District Office, Karanganyar Regency. The t test shows that t_count is 3.429 > t_table 2.028, and the significance level is 0.002 < 0.05, so H_o is rejected and H_1 is accepted. (2) there is an influence of communication on the work spirit of employees at the Tasikmadu District Office, Karanganyar Regency. The t test shows that t_count is 3.928 > t_table 2.028, there is a significance level of 0.000 < 0.05, so H_o is rejected and H_2 is accepted. (3) there is an influence of office layout (layout) and communication on the work spirit of employees at the Tasikmadu District Office, Karanganyar Regency. The results of the F Test data processing show that F_(count ) 37.178 > F_(table ) 3.260, and the significance level is 0.000 < 0.05, so H_o is rejected and H_3 is accepted.